A reduced esophageal epithelial integrity in a subgroup of healthy individuals increases with proton pump inhibitor therapy. Issue 4 (1st May 2018) - Pauwels, Ans; Broers, Charlotte; Vanuytsel, Tim; Pardon, Nicolas; Cocca, Silvia; Roman, Sabine; Zerbib, Frank; Tack, Jan; Farré, Ricard
Abstract : Introduction: Approximately 30% of healthy volunteers (HVs) show dilated intercellular spaces in the esophageal epithelium suggesting a functionally reduced epithelial integrity. We aimed to evaluate the presence of an altered epithelial integrity in HVs and whether physiological acid could explain such a difference. Methods: Biopsies for Ussing chamber experiments were taken between 3 cm and 5 cm proximal to the gastroesophageal junction. Twenty‐four‐hour impedance‐pH (MII‐pH) monitoring was performed in the same 15 HVs. MII‐pH tracings from 24 HVs before and after treatment with esomeprazole (40 mg b.i.d., two weeks), a proton pump inhibitor, were analyzed. Reflux parameters and impedance baseline (IB) at different levels of the esophagus were calculated. Results: Epithelial integrity in the distal esophagus presents a large variability in vivo and in vitro (transepithelial electrical resistance 196.9 ± 16.27Ω. cm 2 ; IB measurements 2022 ± 143.5Ω). Esomeprazole highly suppressed the total acid exposure time (AET) (1.9 (0.8–3.1) vs 0 (0–0)%, p < 0.0001). After splitting our participants into "high" and "low" IB, based on the median value, we observed only in the distal esophagus a higher total AET before (2.8 (1.6–4.8) vs 1.0 (0.5–2.2), p = 0.04) and increased IB values after esomeprazole (1620 (1347–1898) vs 2192 (1784‐2503)Ω, p = 0.002) in the "low" IB group. Conclusion: A subgroup of HVs presents a low epithelial integrity in the distal esophagus probably due to the increased presence of physiological acid reflux. Whether these individuals have a higher chance to develop gastroesophageal reflux disease is unknown. The role of epithelial integrity in symptom perception needs to be further explored.